An Analysis for Efficiency and Loan Loss Provisioning Behaviour of Banking Industry in Japan - WU, YUE (2017)
This dissertation studies the determinants of loan loss provision behavior in Japanese banks during the period of 2010-2016. Four hypotheses are designed in an attempt to test whether income smoothing, capital management and cyclical management have relationship with provisioning behavior in the sample Japanese banks. In particular, this dissertation examine the inclusion of X-efficiency influences the amount of provisions for actual and potential loan losses in Japan’s banking system. In order to achieve this purpose, we successively employ two models which are Stochastic Frontier Analysis (SFA) and Generalized Method of Moments (GMM) to estimate the banks’ efficiency and provisioning behavior. Yet, we find there is no significant relationship between the three hypotheses income smoothing, capital management, cyclical management and loan loss provisioning in the examined Japanese banks. However, cost efficiency is found to be an essential part in loan loss provisioning decisions, the incorporation of this variable is significant in analyzing the Japanese banks’ performance.